Pengaruh Teknologi Informasi dan Inovasi terhadap Daya Saing Perusahaan - Muhammad Bachtiar Ali; Syahrum Agung; Ecin Kuraesin (Universitas 45 Surabaya, 2024)
Diversity of innovation is produced by business owners thanks to creativity, planning and the spirit of innovation. Having a strategy in developing competitiveness is a manifestation of the spirit of innovation. If business owners do not have the spirit of innovation in their business, then the business carried out will be fixated on old strategies. This study aims to determine whether there is an influence between information technology and innovations made by the Dawoon Tea business in Bogor Regency on competitiveness. The method in this research is descriptive quantitative. The research data was sourced from the responses of 70 respondents through the instrument of the proposed questionnaire statement. The collected data was then analyzed with normality test, multiple regression analysis, coefficient of determination, t test and f test. The result of this research is that information technology and innovation partially and simultaneously affect the competitiveness of Dawoon Tea Business.